Neosufisme sebagai Strategi Dakwah Spritual Syaikh Ahmad Shohibul Wafa Tajul Arifin - Fitriyani, Kurnia Nur (Warta Ikatan Sarjana Komunikasi Indonesia, 2025)
Abstract - This study explores the concept of neo-Sufism as a transformative strategy for spritual da'wah (Islamic propagation) through the leadership of Syaikh Ahmad Shohibul Wafa Tajul Arifin (Abah Anom) and the Qadiriyah Naqsyabandiyah Pondok Pesantren Suryalaya. Using a qualitative case study approach with data collected through interviews, document analysis, and hermeneutic interpretation, this paper reveals how neo-Sufism integrates spiritual purification with active social engagement. The findings show that Abah Anom’s da'wah includes spiritual guidance (talqin), moral instruction (tanbih), and institutionalized services such as education, rehabilitation, and public welfare programs. These initiatives not only emphasize individual piety but also promote collective well-being and moral governance. Abah Anom’s model demonstrates that Sufism, when renewed through neo-Sufi principles, can contribute to social transformation, state collaboration, and spiritual resilience in the face of modern challenges. The study offers a framework for contextual Islamic propagation that is inclusive, adaptive, and impactful in both national and transnational settings.Keywords: Neo-Sufism; Social Da'wah; Syaikh Ahmad Shohibul Wafa Tajul Arifin; Tarekat Qadiriyah Naqsyabandiyah; Spiritual Transformation; Islamic Social InstitutionsAbstrak - Penelitian ini mengkaji konsep neosufisme sebagai strategi transformasi dakwah spiritual melalui kepemimpinan Syaikh Ahmad Shohibul Wafa Tajul Arifin (Abah Anom) dalam Tarekat Qadiriyah Naqsyabandiyah Pondok Pesantren Suryalaya. Dengan pendekatan kualitatif studi kasus, serta metode wawancara, analisis dokumen, dan interpretasi hermeneutik, penelitian ini menemukan bahwa neosufisme menggabungkan pemurnian spiritual dengan keterlibatan aktif dalam kehidupan sosial. Dakwah Abah Anom meliputi pembinaan spiritual (talqin), penanaman nilai moral (tanbih), serta layanan sosial yang terinstitusi seperti pendidikan, rehabilitasi, dan program kesejahteraan masyarakat. Pendekatan ini tidak hanya menekankan kesalehan individu, tetapi juga mendorong pembangunan kolektif dan kerja sama dengan negara. Model dakwah yang dibangun menunjukkan bahwa sufisme yang diperbarui melalui prinsip-prinsip neosufisme dapat menjadi kekuatan transformasi sosial dan ketahanan spiritual yang relevan dengan tantangan zaman modern. Studi ini menawarkan kerangka dakwah Islam yang kontekstual, inklusif, dan berdampak di tingkat nasional maupun lintas negara.Kata kunci: Neosufisme; Dakwah Sosial; Syaikh Ahmad Shohibul Wafa Tajul Arifin; Tarekat Qadiriyah Naqsyabandiyah; Transformasi Spiritual; Institusi Sosial Islam.